CAUSES AND CONSEQUENCES OF LATE DIAGNOSIS, TREATMENT OF CONGENITAL HYDRONEPHROSIS IN CHILDREN - F. A, Otamuradov; A.Sh , Vakhidov; S. A , Rakhmonov; Z. Kh, Karimova (Journal of Medical Genetics and Clinical Biology, 2024)
Objective: This study aims to analyze the causes and consequences of late diagnosis of congenital hydronephrosis in children, focusing on its impact on renal function and the outcomes of surgical correction in cases diagnosed after the early stages of childhood. Methods: Retrospective analysis was conducted on 99 children (aged 8 months to 17.5 years) diagnosed with hydronephrosis postnatally, from 2010 to 2023, at the SODMC of Termez. All patients underwent clinical, laboratory, and radiological investigations, including ultrasound, CT scans, and urography, to evaluate the extent of renal involvement and determine appropriate surgical interventions. Results: Late diagnosis, primarily after 3 years of age (73.7% of cases), was linked to a latent disease course, often masked by nonspecific symptoms such as pyelonephritis. Hydronephrosis was more prevalent on the right side (51.5%), with 31.3% of children diagnosed with stage IV disease requiring nephrectomy. The most common etiology included aberrant vessels and pyeloternal segment stenosis. Surgical treatments included pyeloplasty (58.6%), antevasal anastomosis (10.1%), and nephrectomy (22.1%). Postoperative recovery was generally uncomplicated, with 68.6% of children showing reduced renal pelvis size and improved kidney function. Novelty: This study highlights the significant risk of renal damage associated with delayed diagnosis and emphasizes the need for early detection and timely surgical intervention to preserve renal function. It provides valuable insights into the management of hydronephrosis in children, particularly in regions with limited access to advanced diagnostic tools.